2021
DOI: 10.1002/jso.26780
|View full text |Cite
|
Sign up to set email alerts
|

High concordance of 70‐gene recurrence risk signature and 80‐gene molecular subtyping signature between core needle biopsy and surgical resection specimens in early‐stage breast cancer

Abstract: Background and Objectives: With increased neoadjuvant therapy recommendations for early-stage breast cancer patients due to the COVID-19 pandemic, it is imperative that molecular diagnostic assays provide reliable results from preoperative core needle biopsies (CNB). The study objective was to determine the concordance of MammaPrint and BluePrint results between matched CNB and surgical resection (SR) specimens.Methods: Matched tumor specimens (n = 121) were prospectively collected from women enrolled in the F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…When categorizing the Oncotype DX recurrence score into low, intermediate, and high categories, three of eight patients had one core in a higher risk category than the other three cores [ 28 ]. Low intratumoral heterogeneity has also been reported for the EndoPredict [ 29 ] and MammaPrint [ 30 , 31 ] risk of recurrence scores. Results from these studies of intratumoral heterogeneity of multigene scores are comparable to the present study, where there was 81% and 76% intratumoral agreement of ROR-P group and PAM50 subtype, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…When categorizing the Oncotype DX recurrence score into low, intermediate, and high categories, three of eight patients had one core in a higher risk category than the other three cores [ 28 ]. Low intratumoral heterogeneity has also been reported for the EndoPredict [ 29 ] and MammaPrint [ 30 , 31 ] risk of recurrence scores. Results from these studies of intratumoral heterogeneity of multigene scores are comparable to the present study, where there was 81% and 76% intratumoral agreement of ROR-P group and PAM50 subtype, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…Few panellists (18.1%) reported performing BCMS on core biopsies, a surprising finding, given the proven concordance between biopsies and surgical specimens in terms of gene expression profiling with BCMS [27][28][29] . Another unexpected discovery was the increased use of BCMS during the COVID-19 pandemic reported by 14.3% of panellists, particularly for patients with lymph node involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Second, OncotypeDX and MammaPrint have traditionally been used to test surgical resection specimens in the adjuvant setting. However, previous studies reported a moderate-to-strong concordance (ranging from 72% to 91%) of these multigene assays between core needle biopsy and surgical specimens 13 , 14 . Lastly, large prospective studies with planned NACT and multigene assay testing are needed to confirm our findings.…”
mentioning
confidence: 81%